An Eye for Injustice : Robert C. Sims and Minidoka - Stacy, Susan M., 1943-; Sims, Robert C. (Book collections on Project MUSE., 2020)
"The book, about the Minidoka War Relocation Center in Idaho, contains a selection of Robert Sims's published articles, conference papers, speeches, and slide shows on Minidoka and Japanese internment. Includes a new essay documenting the transformation of the forgotten post-WWII patch of desert to the Minidoka National Historical Site; short biographical essays by people who worked with him describing Sims' passion for social justice, history, and education, and an essay about the Robert C. Sims Collection at Boise State University."--